Estimasi Value At Risk (VaR) Kunjungan Wisatawan Mancanegara Ke Sumatera Barat - Maulani, Fiqrah; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2022)
West Sumatra Province has become one of the destinations for foreign tourists to travel. There are many types of tourism in West Sumatra, ranging from cultural tourism, sports tourism, religious tourism, and culinary tourism. Because of this existing tourism potential, it is necessary to estimate the maximum loss from tourist visit revenue. One of the risk management for tourism budget losses is by using the Value at Risk method. Value at Risk , namely estimation of the biggest potential loss for a certain period with a certain level of confidence and normal market conditions. Estimation VaR is carried out for forecasting the number of foreign tourist visits from Jan-Jun 2022 with α=5%. The budget issued by the West Sumatra Provincial Office for tourism development is IDR. 209.481.220,00. Then obtained VaR value of IDR. 112.801.838.04. This means that the biggest loss opportunity borne by the Provincial Government of West Sumatra in the next month from foreign tourist visits to West Sumatra is IDR 112,801,838.04 against a value of IDR 872,400,000.00.